2016
DOI: 10.1007/s10549-016-4080-9
|View full text |Cite
|
Sign up to set email alerts
|

Survival with metastatic breast cancer based on initial presentation, de novo versus relapsed

Abstract: These data provide information that may guide discussions about prognosis between physicians and patients with MBC. In addition, it highlights the importance of stratifying for initial stage at diagnosis in future MBC therapeutic trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
102
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(106 citation statements)
references
References 29 publications
1
102
0
1
Order By: Relevance
“…Considering the differences in traditional concepts among people in different regions, the Chinese are pursuing active and comprehensive treatment, while the Western population is pursuing a higher quality of life, which may have led to the above-mentioned differences in treatment. Prior reports state that the median survival time of patients with MBC was 2-3 years (7,9,(15)(16)(17)(18). Andre et al (7) reported that the median survival time of patients with DnMBC was 23 months in 1987-1993, compared with 29 months in 1994-2000, of which most patients had single metastasis especially bone metastasis, >80% had received chemotherapy and 51% had received local surgery or radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the differences in traditional concepts among people in different regions, the Chinese are pursuing active and comprehensive treatment, while the Western population is pursuing a higher quality of life, which may have led to the above-mentioned differences in treatment. Prior reports state that the median survival time of patients with MBC was 2-3 years (7,9,(15)(16)(17)(18). Andre et al (7) reported that the median survival time of patients with DnMBC was 23 months in 1987-1993, compared with 29 months in 1994-2000, of which most patients had single metastasis especially bone metastasis, >80% had received chemotherapy and 51% had received local surgery or radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…When examining de novo Stage IV patients, the current survival is in the range of 27-29 months. 28,29 Survival is notably higher for hormone receptor positive disease (34 months) and HER2 positive disease (29 months) when compared with triple negative breast cancer (11 months). These results are in line with the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the de novo cohort, 54 patients who underwent primary cancer surgery had significantly better progression-free survival (PFS) and overall survival (OS; hazard ratio [HR] = 0.44; 95% confidence interval [CI]: 0.26-0.72 and HR = 0.49; 95% CI: 0.26-0.93, respectively) than those who did not have surgery [11]. Several other studies that examined clinical features that are associated with long-term survival of HER2 positive MBC treated with HER2-targeted therapies identified hormone receptor positivity, oligometastatic disease, surgical resection of metastases and/or primary tumor, and no prior exposure to HER2-targeted therapies (in the adjuvant setting) as predictors of long-term survival [7][8][9][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This has resulted in overall fewer HER2 positive MBC and in a relative increase in the proportion of de novo stage IV disease among patients with HER2 positive metastatic disease. Historically, de novo stage IV breast cancer accounted for 6%-20% of metastatic breast cancers across subtypes, but recent studies reported that over 50% of metastatic HER2 breast cancers today represent de novo stage IV disease [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%